EKSISTENSI HUKUM ADAT DALAM MENYELESAIKAN KEKERASAAN DALAM RUMAH TANGGA DI DESA PINJAUAN KANAGARIAN PILUBANG KECAMATAN SUNGAI LIMAU KABUPATEN PADANG PARIAMAN - Putri Asri Sri Rahayu; Erdianto Effendi; Mukhlis R (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
Indonesia is a state of law (rechstaat) where the legal provisions rely or are guided by the Pancasila and the 1945 Constitution, as a rule they must not conflict with higher laws because they apply nationally. But in social life besides national law, there are also laws that grow and develop in society, where the law is born from the habits or attitudes and behavior of the people themselves who are often referred to as habits. This custom or habit will develop into a provision called adat law. That customary law still lives in each region. Particularly in the Penagarian Village of Pilubang Village, Sungai Limau Subdistrict, Padang Pariaman District, customary law still exists used by the community in resolving criminal acts of domestic violence. For this reason, the writer is interested in conducting research as a scientific work in the form of a thesis with the title